The Association Between Single-Child Status and Risk of Abdominal Obesity: Result From a Cross-Sectional Study of China - Gao, Di; Li, Yanhui; Yang, Zhaogeng; Ma, Ying; Chen, Manman; Dong, Yanhui; Zou, Zhiyong; Ma, Jun (Frontiers in Pediatrics, 2021)
Background Obesity has become a serious problem threatening the health of children and adolescents, and China’s One-Child Policy has affected family structure and parenting practice, which may result in several adverse health outcomes. The present study aims to investigate the association between single-child status and the risk of abdominal obesity in Chinese adolescents, and also to compare the differences in the risk of unideal energy-related behaviors. Methods Data were obtained from a school-based cross-sectional survey conducted in seven provinces of China, 2012. A total of 31,291 students aged 7-17 years were recruited in this study. Anthropometric measurements were conducted to assess height and waist circumference, and questionnaires were used to obtain information of single-child status, parental educational attainment, parental weight status, and offspring energy-related behaviors. Multivariate logistic regression models were used to estimate the odds ratio (OR) and 95% confidence intervals (95% CI) of single-child status and odds of childhood abdominal obesity and energy-related behaviors. Results The prevalence of abdominal obesity was 18.2% in single children, which was higher than that of not single children (13.7%). The prevalence was also higher in single children in different sex and residence subgroups. Logistic regression models showed that single children had 1.33 times (OR: 1.33, 95%CI: 1.24-1.43, P<0.001) higher odds of abdominal obesity compared to not-single children. Single children had 1.08 times higher odds of physical inactivity (OR: 1.08, 05%CI: 1.03-1.14, P=0.004), 1.13 times higher odds of excessive SSBs consumption (OR: 1.13, 95%CI: 1.05-1.23, P=0.002), and 1.08 times more likely to eat out (OR: 1.08, 95%CI: 1.02-1.13, P=0.005). Those associations were more remarkable in single girls. Conclusion Being a single child may be associated with a higher odds of childhood abdominal obesity and unhealthy energy-related behaviors. Future interventions and strategies to prevent abdominal obesity should focus on this high-risk population.